Development of Kinect- Based Science Learning Media to Support Improvement of Cognitive Learning Outcomes - Fajar Fitri; Laifa Rahmawati (Journal of Science Education Research, 2018)
The purpose of this study is to describe the grant of science based learning media Kinect to support the improvement of students’ learning outcomes from cognitive aspect. This research is an educational development research which is adapted from the development model according to Borg and Gall. The research was conducted in four main stages, that are (1) needs analysis, (2) instructional design, (3) media development, (4) validation. Instruments used in this research are assessment sheets by validator, student response questionnaires, pretests, and post test. After being validated, the media was tested to ten students, so that the results obtained of student responses and the effectiveness of improving students' cognitive learning outcomes. The result of the development is Kinect-based science learning media. From the results of research and development stage as well as experiments that have been done can be concluded that the product can improved student learning outcomes in cognitive aspect